Home parenteral nutrition for people with inoperable malignant bowel obstruction - Sowerbutts, Anne Marie (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effectiveness and safety of home parenteral nutrition in people with inoperable malignant bowel obstruction.